The Effect of Permissive parenting Style on the Main Character’s Emotion and Behavior Reflected in Greta Gerwig’s Lady Bird (2017) - Ana Widiyanti; Najiyah Najiyah (Metaphor, 2022)
The aims of this research are to analyze and find the effect of permissive parenting style on the main character’s emotion and behavior reflected in Greta Gerwig’s’ Lady Bird (2017). In this research, researcher analyzes the psychological condition of the main character. Then the researcher explains the effect of permissive parenting style on the main character reflected in Greta Gerwig’s Lady Bird (2017). The object and primary data of this thesis is the movie entitled Lady Bird (2017). The researcher uses Parenting Style by Diana Baumrind and Psychoanalysis by Sigmund Freud as the grounded theory. This research is descriptive qualitative research. As the result, the researcher found that the effect of permissive parenting style on the main character is lack self-discipline, unable to control emotion, hard to change bad habit, being impulsive, and the vulnerable to delinquency, substance and alcohol abuse. By that finding, it is proven that the effect of permissive parenting style can affect the emotions and behavior of the main character in this film.